Pengetahuan wanita usia subur (wus) tentang covid-19 dan perilaku pencegahannya pada masa pandemi di kecamatan kuta utara badung : Knowledge of woman in childbearing age about covid-19 and their preventive behavior in pandemic in north kuta district, badung - Widiastuti, Ni Made Rai; Agustina, Ni Kadek Tasya (Bali Medika Jurnal, 2021)
Corona virus (COVID-19) is a world health problem and has infected globally, including Indonesia that cause high mortality and morbidity rates. Good knowledge as well as clean and healthy living habits is an effort to prevent the spread of COVID-19. Woman in the family plays a very important role, one of which is to maintain the health of all family members in order to stay healthy, especially during the COVID-19 pandemic. The aim of this study is to determine the description of public knowledge, especially women in childbearing age about COVID-19 pandemic and their preventive behavior during the pandemic. This is a quantitative study with a cross-sectional approach. The survey was conducted to 365 women in North Kuta District, Badung Regency, through purposive sampling. This study used an electronic questionnaire as a data collection tool and the data were analyzed univariately by presenting the variable frequency distribution. The results of the data analysis showed that most of them, 71.3% of respondents with good knowledge category. Most of the 80.6% of respondents got information about COVID-19 through social media and the behavior in preventing the spread of COVID-19 has shown that they comply with health protocols, 92.6% by washing their hands properly, 91.8% by using masks and 88.8% by social distancing.